Conization Using an Electrosurgical Knife for Cervical Intraepithelial Neoplasia and Microinvasive Carcinoma - Xiang, Libing (PLoS One, 2015)
OBJECTIVE: The aim of the present study was to evaluate the incidences of margin involvement, disease relapse, and complications in patients who had undergone conization using an electrosurgical knife (EKC) for cervical intraepithelial neoplasia (CIN) or microinvasive carcinomas (micro-CAs). MATERIALS AND METHODS: A retrospective case series analysis was performed with a total of 1359 patients who underwent EKC in Fudan University Shanghai Cancer Center between June 2004 and July 2010. RESULTS: The median age of the patients was 39 years old (range: 19-72). Conization revealed the presence of CIN in 1113 (81.9%) patients, micro-CA in 72 (5.3%) patients and invasive carcinomas in 44 (3.2%) patients. The remaining 130 (9.6%) patients were free of diseases in the cone specimens. Positive surgical margins, or endocervical curettages (ECCs) were found in 90 (7.6%) patients with CINs or micro-CAs. Three factors were associated with positive margins and ECCs and included age (>50 years; odds ratio (OR), 3.0, P<0.01), postmenopausal status (OR, 3.1, P<0.01) and microinvasive disease (OR, 2.7, P<0.01). One thousand and eighty-nine (92.0%) patients were followed-up regularly for a median follow-up duration of 46 months (range: 24-106 months). Disease relapse was documented in 50 (4.6%) patients. Eighty-two (6.0%) cases experienced surgical complications that needed to be addressed, including early or late hemorrhages, infections, cervical stenosis, etc. CONCLUSIONS: Our patients demonstrated that EKC was an alternative technique for diagnosis and treatment of CIN or micro-CAs with relatively low rate of recurrence and acceptable rate of complications. A randomized clinical trial is warranted to compare EKC, CKC and LEEP in the management of CIN or micro-CA.